CD28 Individual Signaling Up-regulates Human IL-17A Expression by Promoting the Recruitment of RelA/NF-κB and STAT3 Transcription Factors on the Proximal Promoter - Kunkl, Martina; Mastrogiovanni, Marta; Porciello, Nicla; Caristi, Silvana; Monteleone, Emanuele; Arcieri, Stefano; Tuosto, Loretta (Frontiers in Immunology, 2019)
CD28 is an important co-stimulatory receptor for T lymphocytes that, in humans, delivers TCR-independent signal leading to the up-regulation of pro-inflammatory cytokines. We have recently reported that CD28 autonomous signaling induces the expression of IL-17A in peripheral CD4+ T lymphocytes from healthy donors, multiple sclerosis, and type 1 diabetes patients. Due to the relevance of IL-17A in the pathophysiology of several inflammatory and autoimmune diseases, we characterized the mechanisms and signaling mediators responsible for CD28-induced IL-17A expression. Here we show that CD28-mediated up-regulation of IL-17A gene expression depends on RelA/NF-κB and IL-6-associated STAT3 transcriptions factors. In particular, we found that CD28-activated RelA/NF-κB induces the expression of IL-6 that, in a positive feedback loop, mediates the activation and nuclear translocation of tyrosine phosphorylated STAT3 (pSTAT3). pSTAT3 in turn cooperates with RelA/NF-κB by binding specific sequences within the proximal promoter of human IL-17A gene, thus inducing its expression. Finally, by using specific inhibitory drugs, we also identified class 1A phosphatidylinositol 3-kinase (PI3K) as a critical upstream regulator of CD28-mediated RelA/NF-κB and STAT3 recruitments and trans-activation of IL-17A promoter. Our findings reveal a novel mechanism by which human CD28 may amplify IL-17A expression in human T lymphocytes and provide biological bases for immunotherapeutic approaches targeting CD28-associated class 1A PI3K to dampen IL-17A-mediated inflammatory response in autoimmune/inflammatory disorders.